Limit states of materials and structures : direct methods - Dieter, Weichert. (Springer, 2017)
To determine most exactly the carrying capacity of a structure or a structural element has always been a major concern to any design engineer. For safety sensitive structures this implies not only situations of normal service conditions but also states near to failure or post-critical states in order to better prevent accidents by appropriate design. Among the rational design tools available to engineers, for this purpose the so-called "direct methods", embracing in particular limit- and shakedown analysis, have always been particularly attractive due to the fact that they allow to determine in a constructive way directly the limit loads of a structure. This holds true for simple loading by proportionally applied mechanical and thermal loads, but also for the more complicated situation of variable loading even in the case when the loading history is not deterministically given.